2013
DOI: 10.1371/journal.pone.0057285
|View full text |Cite|
|
Sign up to set email alerts
|

Curcumin Modulates the Inflammatory Response and Inhibits Subsequent Fibrosis in a Mouse Model of Viral-induced Acute Respiratory Distress Syndrome

Abstract: Acute Respiratory Distress Syndrome (ARDS) is a clinical syndrome characterized by diffuse alveolar damage usually secondary to an intense host inflammatory response of the lung to a pulmonary or extrapulmonary infectious or non-infectious insult often leading to the development of intra-alveolar and interstitial fibrosis. Curcumin, the principal curcumoid of the popular Indian spice turmeric, has been demonstrated as an anti-oxidant and anti-inflammatory agent in a broad spectrum of diseases. Using our well-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
121
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(126 citation statements)
references
References 79 publications
3
121
0
2
Order By: Relevance
“…In addition, curcumin has been shown to induce antioxidant activity not only by scavenging reactive oxygen and nitrogen species, but also by induction of antioxidant enzymes expression [3]. Together with its innocuous, inexpensive and easily available properties, the therapeutic effect of curcumin has been widely studied in numerous diseases such as acute lung injury [15], acute respiratory distress syndrome [4] and allergic asthma [6]. As chronic inflammation and oxidative stress in the lung are thought to be key components of the pathogenesis of COPD, curcumin may play a protective role in the development of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, curcumin has been shown to induce antioxidant activity not only by scavenging reactive oxygen and nitrogen species, but also by induction of antioxidant enzymes expression [3]. Together with its innocuous, inexpensive and easily available properties, the therapeutic effect of curcumin has been widely studied in numerous diseases such as acute lung injury [15], acute respiratory distress syndrome [4] and allergic asthma [6]. As chronic inflammation and oxidative stress in the lung are thought to be key components of the pathogenesis of COPD, curcumin may play a protective role in the development of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that curcumin has antifibrotic effects on cardiac fibrosis in spontaneously hypertensive rats via PPAR-γ activation[15]; on liver fibrosis in carbon tetrachloride treated rats via inhibition of transforming growth factor 1 and connective tissue growth factor expression[16], suppressing cannabinoid receptor type-1 [17], as well as ameliorating intrahepatic angiogenesis [18]; on renal fibrosis in unilateral ureteral obstruction (UUO) rat via inhibiting of nuclear factor kappa-B and activator protein-1[19] and in 5/6 nephrectomized rat via modulating Nrf2-Keap1 pathway [20]; on pulmonary fibrosis in viral-induced acute respiratory distress syndrome mice through the alteration of inflammation and myofibroblast differentiation [21] and in bleomycin treated mice via overexpression of cathepsins K and L [22]. …”
Section: Introductionmentioning
confidence: 99%
“…-SD rats (BLM, 7.5 U/kg) Tang et al (2016) Astragalin Diospyros kaki L.f. -Wistar rats (BLM, 2.5 mg/kg), ICR mice (LPS, 5 mg/kg) - Akgedik et al (2012) and Zhang et al (2015) Curcumin Curcuma longa L. PMVEC, primary FB (IR, 2 Gy) C57BL/6 mice (0.5 μg LPS or 13.5 Gy IR), CBA/J mice (reovirus 1/L, 10 7 PFU) FB (TGF-β, 6 ng/ml), PF patients Lee et al (2010), Smith et al (2010), Avasarala et al (2013) and Jiang and Zhang (2015a) EGCG Camellia sinensis (L.) Kuntze FB WI−38 (TGF-β1, 10 ng/ml) Wistar rats (BLM, 6.5 U/kg), SD rats (IR, 22 Gy) - Sriram et al (2009aSriram et al ( , 2009bSriram et al ( , 2015 and You et al (2014) Corilagin Caesalpinia coriaria (Jacq. )…”
Section: Scutellaria Baicalensismentioning
confidence: 99%
“…Moreover, 1% curcumin significantly decreased TNF-α level in BALF from LPS-challenged mice; the decrease was more pronounced when curcumin was given at a dose of 5% (Lee et al, 2010). Using the model of reovirus 1/L-induced acute viral pneumonia which displays many characteristics of human acute respiratory distress syndrome (ARDS)/ALI, female CBA/J mice were treated with curcumin (50 mg/kg) 5 days prior to intranasal inoculation with 10 7 PFU reovirus 1/L and daily, thereafter (Avasarala et al, 2013). The study showed that curcumin treatment in vivo effected both inflammatory (diffuse alveolar damage) and fibrotic lesion development leading to a significant reduction in the development of ALI/ARDS in reovirus 1/Linfected mice, potentially via the modulation of cytokine/chemokine expression through the NF-κB pathway as well as the host fibrotic response during the regeneration phase of the disease through modulation of the TGF-β pathway (Avasarala et al, 2013).…”
Section: Phenolsmentioning
confidence: 99%